Industry Council Plan and « Mater et Magistra » / La démocratie organique et l'encyclique Mater et Magistra - Dion, Gérard (Relations industrielles / Industrial Relations, 1961)
SummaryThe author examines the evolution of the Catholic Social Doctrine on the Industry Council Plan. This paper, while general in outlook and scope, must be read in light of the fact that it was first presented as a communication at the Catholic Social Life Conference, Halifax, October 1961.